Sex Differences in the Diagnosis Latency of Parkinson S Disease in Latin America - Chana-Cuevas, P (Elsevier Ltd, 2025)
Background: Age and sex are known risk factors for Parkinson s Disease (PD), but it remains controversial if there are sex differences in the diagnosis latency. The objective of this study was to examine these sex differences in Latin America. Methods: The Latin American Research Consortium on the Genetics of PD (LARGE-PD) includes PD patients from countries across Latin America who were diagnosed using the UK Brain Bank criteria. Ages at onset (AAO; N = 2,792), diagnosis (AAD; N = 1,416), and calculated diagnosis latency (N = 1,416) were extracted from the LARGE-PD database and compared for both males and females overall, by country, and decade-long age ranges. A cohort was created based on available data for motor sign at onset (N = 492). Regressions examining diagnosis latency as a factor of sex, country, and motor subtype were performed. Two-tailed t-tests at 95 % confidence intervals were used to identify differences in mean AAOs, AADs, and diagnosis latencies between the sexes. Results: Across the LARGE-PD cohort, lower AAD was observed in males. Per country, AAO was lower for males in Mexico and diagnosis latency was shorter for males in Chile. Overall, younger females (≤39) and older males (≥70) are likely to experience longer latencies. Conclusions: Our results suggest that there may be country and age dependent sex differences in AAO, AAD, and diagnosis latency of PD in Latin America. Interestingly, the mean AAO of LARGE-PD is approximately 6 years younger than studies done with European populations. Analyses with additional data are needed to determine the influence of other factors. © 2025 The Authors
Keywords: AAO; Age at diagnosis; Age at onset; Diagnosis latency; Latin America; Latino; Parkinson s disease; Sex differences